2012
DOI: 10.1128/iai.00945-12
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphisms in the Fc Gamma Receptor IIIA and Toll-Like Receptor 9 Are Associated with Protection against Severe Malarial Anemia and Changes in Circulating Gamma Interferon Levels

Abstract: An understanding of the immunogenetic basis of naturally acquired immunity to

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 65 publications
1
8
0
Order By: Relevance
“…Our study revealed no association between the FcγRIIIA-176F/V polymorphism and susceptibility to SMA in this pediatric population. This may imply that this particular variant is not independently associated with susceptibility to SMA which is consistent with our previous study involving the combined effect of toll-like receptor 9 and FcγRIIIA polymorphisms [ 39 ]. The FcγRIIIB is a C-terminus linked glycosylphosphatidylinositol (GPI) moiety anchored receptor, exclusively expressed on neutrophils with three characterized allotypes i.e.…”
Section: Discussionsupporting
confidence: 90%
“…Our study revealed no association between the FcγRIIIA-176F/V polymorphism and susceptibility to SMA in this pediatric population. This may imply that this particular variant is not independently associated with susceptibility to SMA which is consistent with our previous study involving the combined effect of toll-like receptor 9 and FcγRIIIA polymorphisms [ 39 ]. The FcγRIIIB is a C-terminus linked glycosylphosphatidylinositol (GPI) moiety anchored receptor, exclusively expressed on neutrophils with three characterized allotypes i.e.…”
Section: Discussionsupporting
confidence: 90%
“…Phagocytosis of parasitic products, such as P. falciparum -derived haemozoin ( Pf Hz), alters inflammatory mediator production and promotes suppression of erythropoiesis [11,12]. Our previous genetic investigations in Kenyan children demonstrate that polymorphic variability in host immune response genes can impart functional changes in inflammatory mediator production that influence susceptibility to SMA [[13], [14], [15], [16], [17], [18]]. We recently used an unbiased approach to further identify genes and gene pathways involved in the pathogenesis of SMA by performing high-throughput genotyping and whole transcriptome in a subset of Kenyan children with discrete mild and severe malaria phenotypes.…”
Section: Introductionmentioning
confidence: 99%
“…Hemophagocytic macrophages that appeared in response to infection, had markers of anti-inflammatory M2 phenotype [ 114 ]. Genetic mutations may predispose patients to the development of hemophagocytes in response to infections [ 107 , 115 ].…”
Section: Nutritional Immunity and Infection-induced Anemiamentioning
confidence: 99%